The Adoption Of Halal Standards Towards The Performance Of Malaysian Food Manufacturing SMEs - Azmi, Fadhlur Rahim (2017)
Increasing Muslim community in Malaysia causes the need for Halal product demand to grow. The Malaysian Government is committed to this Halal industry and is keen to create an international Halal Hub that will operate in Malaysia. Small and Medium Enterprises (SMEs) have the potential to serve as one of the platforms for the hub as various forms of assistance have been provided by the government to ensure that SMEs are more competent and competitive io line with international requirements. The Halal Standards in this study have been outlined as a guideline for research management innovation and the effect is very less emphasized at the moment. A total of 183 SMEs comprising the food industry in Malaysia were selected as samples for this study. Among the questions raised to these SMEs are "what are the key determinants of adopting these Halal standards on improving their performance"? To determine Halal standards factors, the study utilized an exploratory factor analysis to assess the structural factors of the scale. The study also used regression analysis to test the key determinants and the extent to which the use of Halal standards improves SME performance. The results of this study showed that the behavioral factors in the organization towards Halal standards could be clearly comprehended from this developed model. This study also provides advantages over the acceptance of innovation management (Halal standards), organizational management performance and its implications on Halal practices. This in turn helps the government or policy makers to understand in greater details the key contributors to the acceptance of general innovation management and Halal standards, particularly towards improving the performance of SME industry in global realms.